2009
DOI: 10.1051/0004-6361/200810853
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale oscillations in a quiescent prominence observed by HINODE/SOT

Abstract: Context. Investigations of the behavior of small-scale threads can provide an alternative approach to studying prominence dynamics and understanding its origin and nature. Aims. The behavior of threads are analyzed in a quiescent prominence, including drifting and both the horizontally and vertically oscillating motions. These indicate waves in the solar prominence. Methods. We used the Hα images at a setting wavelength of +0.076 Å. A quiescent prominence was observed by HINODE/SOT on 2008 January 15 for about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 44 publications
11
82
0
1
Order By: Relevance
“…Similar results have been obtained recently by Mashnich et al (2009). The same behavior is found in high-resolution Doppler time series from individual filaments threads (Lin 2004) and in Hinode/SOT observations by Ning et al (2009a) who reported a maximum number of 8 periods before the oscillations disappeared. More extense reviews about the damping of small-amplitude prominence oscillations can be found in Oliver (2009), Ballester (2010) and Arregui & Ballester (2010).…”
Section: Introductionsupporting
confidence: 89%
“…Similar results have been obtained recently by Mashnich et al (2009). The same behavior is found in high-resolution Doppler time series from individual filaments threads (Lin 2004) and in Hinode/SOT observations by Ning et al (2009a) who reported a maximum number of 8 periods before the oscillations disappeared. More extense reviews about the damping of small-amplitude prominence oscillations can be found in Oliver (2009), Ballester (2010) and Arregui & Ballester (2010).…”
Section: Introductionsupporting
confidence: 89%
“…Ning et al (2009) report threads in prominences exhibiting vertical and horizontal motions from Hinode/SOT observations close to the Hα line centre at 6563+0.076 Å, and the predominant period of the small-amplitude velocity oscillations is about five minutes. Berger et al (2010) have recently reported smallscale turbulent upflows in quiescent prominences observed with Hinode/SOT, in the Ca II H line at 3969 Å and the Hα line at 6563 Å.…”
Section: Introductionmentioning
confidence: 86%
“…Wiehr et al 1989;Molowny-Horas et al 1998;Terradas et al 2002;Vršnak et al 2007;Ning et al 2009) have discussed damped oscillations in quiescent filaments, disappearing after a few periods, i.e. quickly damped by one or several mechanisms (Oliver 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reference Period (min) Blanco et al (1999) 1 -6 Régnier et al (2001) 5 -65 Foullon et al (2004) 720 Pouget et al (2006) up to 360 Okamoto et al (2007) 2 -4.5 20 -40 Ning et al (2009) 3.5 -6…”
Section: Space-based Observationsmentioning
confidence: 99%